Swimming induced pulmonary oedema in athletes - a systematic review and best evidence synthesis - Erik Hohmann; Vaida Glatt; Kevin Tetsworth (BMC, 2018)
Abstract Background Swimming induced pulmonary oedema is an uncommon occurrence and usually presents during strenuous distance swimming in cold water. The prevalence is most likely underreported and the underlying mechanisms are controversial. The purpose of this study was to summarize the evidence with regards to prevalence, pathophysiology and treatment of swimming induced pulmonary oedema in endurance athletes. Methods Medline, Embase, Scopus and Google Scholar were searched and level I-IV from 1970 to 2017 were included. For clinical studies, only publications reporting on swimming-induced pulmonary oedema were considered. Risk of bias was assessed with the ROBINS-I tool, and the quality of evidence was assessed with the Cochrane GRADE system. For data synthesis and analysis, a best evidence synthesis was used. Results A total of 29 studies were included (174 athletes). The most common symptom was cough, dyspnoea, froth and haemoptysis. The risk of bias for the clinical studies included 13 with moderate risk, 3 with serious, and 4 with critical. Four of the pathophysiology studies had a moderate risk, 3 a serious risk, and 1 a critical risk of bias. A best evidence analysis demonstrated a strong association between cold water immersion and in increases of CVP (central venous pressure), MPAP (mean pulmonary arterial pressure), PVR (peripheral vascular resistance) and PAWP (pulmonary arterial wedge pressure) resulting in interstitial asymptomatic oedema. Conclusion The results of this study suggest a moderate association between water temperature and the prevalence of SIPE. The presence of the clinical symptoms cough, dyspnoea, froth and haemoptysis are strongly suggestive of SIPE during or immediately following swimming. There is only limited evidence to suggest that there are pre-existing risk factors leading to SIPE with exposure to strenuous physical activity during swimming. There is strong evidence that sudden deaths of triathletes are often associated with cardiac abnormalities.